2015
DOI: 10.3390/molecules200917093
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Anti-Quorum Sensing Molecular Composition Derived from Quercus cortex (Oak bark) Extract

Abstract: Abstract:Quercus cortex (Oak bark) has been used in European folk medicine since medieval times for treatment of diarrhea, stomatitis, pharyngitis and skin inflammations. Its antimicrobial activity is a well-known therapeutic property of oak bark, and its novel anti-quorum sensing (QS) ability has also been described recently. In this study, we examined the bioactive compounds of Quercus cortex extract and compared their direct antibacterial and regulatory anti-QS effects against Chromobacterium violaceum CV02… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 35 publications
2
36
0
3
Order By: Relevance
“…The high content in tannins is responsible for the antidiarrheal properties (Reichling et al, 2008). Oak bark extracts furthermore possess antibacterial and anti-quorum sensing activities (Deryabin and Tolmacheva, 2015).…”
Section: Chamomile Flowers (Matricaria Chamomilla L Matricariae Flos)mentioning
confidence: 99%
“…The high content in tannins is responsible for the antidiarrheal properties (Reichling et al, 2008). Oak bark extracts furthermore possess antibacterial and anti-quorum sensing activities (Deryabin and Tolmacheva, 2015).…”
Section: Chamomile Flowers (Matricaria Chamomilla L Matricariae Flos)mentioning
confidence: 99%
“…It is reported that gram-positive bacteria are more sensitive to plant-based extracts rich in tannin-like substances [28,29]. It is also confirmed by properties of compounds earlier found in Quercus cortex extract [12,13].…”
Section: Weigh (G) Dynamics In Crossmentioning
confidence: 55%
“…One of obstacles for use of phytogenic compounds is instable chemical composition of plant extracts depending on growing conditions, ecosystem, and other factors. Earlier, several compounds from oak bark extract (Quercus cortex) having both antibacterial and anti-QS activity [12,13] was found. These substances were used in tests on agricultural poultry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Кроме того, лекарственные растения являются ингибиторами системы чувствительности кворума (QS) у бактерий [10]. Такие ингибиторы обнаружены в экстракте коры Quercus [9]. В то же время известно, что экзогенные ферменты не только повышают продуктивность сельскохозяйственных животных, но и способствуют развитию бактериальной флоры в желудочно-кишечном тракте и тем самым косвенно влияют на популяцию бактерий [3,11].…”
unclassified